Hypolipidemic and Hypoglycemic Potentials of Garlic Extract in High-Fat Diet and Streptozotocin-Induced Wistar Rats - Girsang, Ermi; Chiuman, Linda; Lie, Veronica; Puspita, Sunny (Poltekkes Kemenkes Tanjung Karang, 2025)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by elevated blood glucose levels and often associated with hypercholesterolemia. Garlic (Allium sativum Linn.), rich in bioactive compounds such as allicin, saponins, and flavonoids, has been widely reported to possess lipid- and glucose-lowering properties. This study aimed to evaluate the hypolipidemic and hypoglycemic effects of garlic extract in Wistar rats subjected to a high-fat diet and streptozotocin (STZ) induction. A laboratory experimental design with a post-test-only control group was employed. For cholesterol assessment, hypercholesterolemic rats were administered garlic extract at doses of 0.05, 0.10, and 0.20g/head/day, while diabetic rats induced with STZ received doses of 100, 250, and 500 mg/kg body weight per day, with corresponding control groups. Garlic extract significantly reduced mean cholesterol levels in a dose-dependent manner (130.60mg/dL, 121.80mg/dL, and 112.00mg/dL for 0.05, 0.10, and 0.20g/head/day, respectively). In contrast, mean blood glucose levels showed a marginal decrease with increasing doses (282.80 mg/dL, 271.20mg/dL, and 269.27mg/dL at 100, 250, and 500mg/kgBW/day, respectively). However, no statistically significant differences were observed among groups (p=0.706, one-way ANOVA). These findings suggest that garlic extract exhibits a potent cholesterol-lowering effect in hypercholesterolemic rats but has a limited impact on blood glucose reduction under the tested conditions. Further studies are warranted to determine the optimal dosage and underlying mechanisms of action.